Sagittal spinal alignment in patients with lumbar disc herniation - Endo, Kenji; Suzuki, Hidekazu; Tanaka, Hidetoshi; Kang, Yupeng; Yamamoto, Kengo (European spine journal, 2010)
A retrospective cross-sectional study was designed to evaluate total sagittal spinal alignment in patients with lumbar disc herniation (LDH) and healthy subjects. Abnormal sagittal spinal alignment could cause persistent low back pain in lumbar disease. Previous studies analyzed sciatic scoliotic list in patients with lumbar disc herniation; but there is little or no information on the relationship between sagittal alignment and subjective findings. The study subjects were 61 LDH patients and 60 age-matched healthy subjects. Preoperative and 6-month postoperatively lateral whole-spine standing radiographs were assessed for the distance between C7 plumb line and posterior superior corner on the top margin of S1 sagittal vertical axis (SVA), lumbar lordotic angle between the top margin of the first lumbar vertebra and first sacral vertebra (L1S1), pelvic tilting angle (PA), and pelvic morphologic angle (PRS1). Subjective symptoms were evaluated by the Japanese Orthopedic Association (JOA) score for lower back pain (nine points). The mean SVA value of the LDH group (32.7 ± 46.5 mm, ± SD) was significantly larger than that of the control (2.5 ± 17.1 mm), while L1S1 was smaller (36.7 ± 14.5°) and PA was larger (25.1 ± 9.0°) in LDH than control group (49.0 ± 10.0° and 18.2 ± 6.0°, respectively). At 6 months after surgery, the malalignment recovered to almost the same level as the control group. SVA correlated with the subjective symptoms measured by the JOA score. Sagittal spinal alignment in LDH exhibits more anterior translation of the C7 plumb line, less lumbar lordosis, and a more vertical sacrum. Measurements of these spinal parameters allowed assessment of the pathophysiology of LDH.